O CONTEÚDO FORMAL NA REPRESENTAÇÃO IMAGÉTICA DOS MODELOS ATÔMICOS - Neto, Odone Gino Zago (2018)
The proposal of this research is to relate the imagery representation building of the atom with the formal content of the studied Chemistry in high school. The audience was private school students of Santa Maria, RS, and through the elaboration of drawings of atoms and molecules has been examined for the presence of Chemical content as: Atomic models, electrical characteristic of matter and links among atoms. The study used as references the learning theories of Lev Vigotsky and object-model theories of Mario Bungue. It was investigated the level of development and understanding of atomic structure and itsr application in the studies of chemistry. As a way to justifiy the relevance of this research due to the constant traffic of chemistry studies formal to the different visible and invisible universes. In this perspective, the invisible to the eye, created and imagined in the mind of man, explains the facts studied in laboratory. To understand how the student does this transition is necessary to verify how he imagines the world invisible to the eye and how he applies this knowledge in understanding of the visible world. The methodological procedures characterizing a qualitative and quantitative research of study type case based on the elaboration, by students, of drawings of atoms and molecules and subsequent application of a questionnaire. The analysis of the survey`s data showed that the pictographic representation used to draw the atoms was a more complex Atomic model, on the other hand, the imagery representation of molecules stick to the simplest model. It was verified that there is still excellence in eletrosfera the representation, but not the core. It is observed that many participants of research have clarified the idea of model, however, a vast majority use them constantly to better understand the chemistry.